Harold finds a voice - Dicmas, Courtney (Child's Play Inc., 2013)
"Harold is an amazing mimic, and can imitate the sound of everything in his home. Tired of repeating the same old noises, he yearns to find out what other voices there are in the big, wide world. But what happens when he suddenly realizes that he doesn't yet have a voice of his own?"--Cover p. 4.